2018
DOI: 10.1080/07347332.2018.1543376
|View full text |Cite
|
Sign up to set email alerts
|

Couples coping with screening burden and diagnostic uncertainty in Li-Fraumeni syndrome: Connection versus independence

Abstract: Purpose: Li-Fraumeni Syndrome (LFS) is an inherited tumor predisposition syndrome with lifetime cancer risks approaching 100% and evolving risk-management strategies. This study evaluated couples’ coping with LFS-related burdens. Research approach: Constructivist grounded theory and anticipatory loss frameworks guided design and analysis. Sample and methods: Twenty-six individuals enrolled in the NCI LFS Family Study completed semi-structured interviews with their partner during annual screening visits. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…variants (Batalini et al, 2019;Fortuno, James, & Spurdle, 2018), and cancer surveillance for people with TP53 pathogenic germline variants is time intensive and emotionally stressful (Ballinger et al, 2017;Kratz et al, 2017;Pantaleao et al, 2019;Villani et al, 2016;Young et al, 2019). Therefore, robust TP53 variant classification is essential for optimal clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…variants (Batalini et al, 2019;Fortuno, James, & Spurdle, 2018), and cancer surveillance for people with TP53 pathogenic germline variants is time intensive and emotionally stressful (Ballinger et al, 2017;Kratz et al, 2017;Pantaleao et al, 2019;Villani et al, 2016;Young et al, 2019). Therefore, robust TP53 variant classification is essential for optimal clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to an increased number of variants of uncertain significance identified in TP53, including in cancer patients who do not meet LFS criteria, and individuals without cancer (Bittar et al, 2019). Given the significant clinical and emotional challenges that come with an LFS diagnosis (Ballinger et al, 2017;Evans et al, 2006;Kratz et al, 2017;Schon & Tischkowitz, 2018;Villani et al, 2016;Young et al, 2019), it is essential to correctly assign TP53 germline variant pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…The task of the TP53 VCEP was to specify the ACMG/AMP guidelines to assist with the clinical classification of variants in the TP53 gene. There is a rapidly growing number of individuals without personal or family history consistent with LFS who have germline TP53 variants (Batalini et al, 2019; Fortuno, James, & Spurdle, 2018), and cancer surveillance for people with TP53 pathogenic germline variants is time intensive and emotionally stressful (Ballinger et al, 2017; Kratz et al, 2017; Pantaleao et al, 2019; Villani et al, 2016; Young et al, 2019). Therefore, robust TP53 variant classification is essential for optimal clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to an increased number of variants of uncertain significance identified in TP53 , including in cancer patients who do not meet LFS criteria, and individuals without cancer (Bittar et al, 2019). Given the significant clinical and emotional challenges that come with an LFS diagnosis (Ballinger et al, 2017; Evans et al, 2006; Kratz et al, 2017; Schon & Tischkowitz, 2018; Villani et al, 2016; Young et al, 2019), it is essential to correctly assign TP53 germline variant pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has begun to illuminate the psychosocial effects on families living with LFS (Forbes Shepherd et al, 2018), but no specific patterns have emerged in which family members share the burden of cancer screening and risk management that providers can encourage in the families with whom they work (Peters et al, 2016; Ross et al, 2017). Recent literature regarding family coping with hereditary cancer stressors has reported that relatives often shift roles to meet new challenges; for example, members of a couple alternating leadership burdens or providing emotional support for the other’s distress related to LFS (Coyne et al, 2012; Young et al, 2018). The present study indicated that while one member filled a health leader role, others were sensitive to the demands that role placed on the individual and often offered support or even shifted into that role.…”
Section: Discussionmentioning
confidence: 99%